Mufasir Digital di Ruang Virtual: Tren Mazhab Tekstualis, Moderat, dan Revisionis di Youtube Indonesia - Abdul Karim; Mukhamad Agus Zuhurul Fuqohak (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
This article analyzes the emerging trends of interpretation on YouTube and their impact on the religious paradigm within Indonesian society. Employing a phenomenological approach that grounds itself in the lived and felt experiences shaping reality, this research identifies three distinct schools of virtual interpretation studies. Firstly, the exclusive textualist school, exemplified by MTA. Secondly, the moderate school, which manifests as a spectrum with two poles: 1) The minimal pole, represented by moderates such as Abdul Somad and Adi Hidayat, who maintain proximity to textualists. 2) The maximum pole, where moderates like Quraish Shihab and Bahauddin Nursalim strike a balance between text and context. Lastly, the revisionist school, embodied by Mun’im Sirry. The implications of these three schools extend to the public paradigm, as followers of the textualist-exclusive school may adopt an exclusive stance, while the liberal revisionist school could potentially encourage permissiveness in society. Conversely, the synthesis of text and context is likely to cultivate a moderate attitude among the audience.